Pengembangan Soal Hots Pada Materi Sistem Pencernaan Manusia Kelas VIII SMP/MTs - Fachrurrozi, Achmad; Wijayadi, Andri Wahyu (Ed-Humanistics : Jurnal Ilmu Pendidikan, 2022)
The problem in this research is motivated by data about daily assessment questions that still use low-level abilities (LOTS), while 21st century learning requires students to have higher-order thinking skills. This research aims to develop and determine the theoretical and empirical validity of the HOTS questions on the human digestive system for class VIII SMP/MTs. The research conducted is a type of research development, this research produces HOTS questions on the Human Digestive System. The development of this HOTS question refers to the ADDIE model development procedure which consists of five stages, (analyze), (design), (development), (implementation) and (evaluation). This development research produces a product HOTS questions on the material of the human digestive system class VIII, which consists of 8 questions. The results of the average score percentage of theoretical validity by material experts, construction experts, and science teachers are 95.3%, 94.7%, and 98.7%, very valid categories. and empirical validity which contains the validity of the items with 8 questions declared valid, with an average score of 0.597, Reliability resulting in an average score of 0.627 being declared reliable, Distractor producing an average score of 18.7% with poor criteria, and discriminating power produce an average score of 0.35% with sufficient criteria. This shows that the product of HOTS questions that have been developed is feasible to use.